MDGA2 is a novel tumour suppressor cooperating with DMAP1 in gastric cancer and is associated with disease outcome. Issue 10 (23rd July 2015) - Wang, Kunning; Liang, Qiaoyi; Li, Xiaoxing; Tsoi, Ho; Zhang, Jingwan; Wang, Hua; Go, Minnie Y Y; Chiu, Philip W Y; Ng, Enders K W; Sung, Joseph J Y; Yu, Jun
Abstract : Background: Using the promoter methylation assay, we have shown that MDGA2 (MAM domain containing glycosylphosphatidylinositol anchor 2) is preferentially methylated in gastric cancer. We analysed its biological effects and prognostic significance in gastric cancer. Methods: MDGA2 methylation status was evaluated by combined bisulfite restriction analysis and bisulfite genomic sequencing. The effects of MDGA2 re-expression or knockdown on cell proliferation, apoptosis and the cell cycle were determined. MDGA2 interacting protein was identified by mass spectrometry and MDGA2-related cancer pathways by reporter activity and PCR array analyses. The clinical impact of MDGA2 was assessed in 218 patients with gastric cancer. Results: MDGA2 was commonly silenced in gastric cancer cells (10/11) and primary gastric cancers due to promoter hypermethylation. MDGA2 significantly inhibited cell proliferation by causing G1–S cell cycle arrest and inducing cell apoptosis in vitro, and suppressed xenograft tumour growth in both subcutaneous and orthotopic xenograft mouse models (both p<0.001). The anti-tumorigenic effect of MDGA2 was mediated through direct stabilising of DNA methyltransferase 1 associated protein 1 (DMAP1), which played a tumour suppressive role in gastric cancer. This interaction activated their downstream key elements of p53/p21 signalling cascades. Moreover, promoter methylation of MDGA2 was detected in 62.4% (136/218) of gastric cancers. Multivariate analysis showed that patients with MDGA2 hypermethylation had a significantly decreased survival (p=0.005). Kaplan–Meier survival curves showed that MDGA2 hypermethylation was significantly associated with shortened survival in patients with early gastric cancer. Conclusions: MDGA2 is a critical tumour suppressor in gastric carcinogenesis; its hypermethylation is an independent prognostic factor in patients with gastric cancer.